O ritmo da manhã na pedagogia Waldorf como articulador do corpo, movimento e conteúdos curriculares na aprendizagem das crianças - Cravo, Felipe Henrique (Universidade Federal de São Carlos, 2025)
This qualitative research, of bibliographic nature, investigates the role of the morning rhythm in Waldorf Education as an articulator of the body, movement, and curricular content in children’s learning. The aim of this study is to understand how this daily practice, structured through rhythmic, musical, bodily, and imagetic elements, contributes to the student’s integral development and to a meaningful experience of the content. The theoretical framework is grounded in the principles of Anthroposophy developed by Rudolf Steiner, as well as in authors who discuss human development, movement, rhythm, and learning from the perspective of Waldorf Education. The methodology consists of a bibliographic study based on works by Rudolf Steiner and other scholars in the field, complemented by the analysis of detailed observations conducted during mandatory teaching internships in elementary education. The results indicate that the morning rhythm is not merely an introductory moment or a supplementary pedagogical practice within the school routine, but a fundamental pedagogical device that integrates body, feeling, and thinking, strengthening the will to learn and preparing the student for subsequent cognitive work. It is concluded that the morning rhythm organically and intentionally articulates movement, aesthetic experience, and curricular content, constituting a pedagogical practice aligned with the anthroposophical conception of human development that guides Waldorf Education.
The morning rhythm in Waldorf Education as an articulator of the body, movement, and curricular content in children's learning
Keywords: Pedagogia Waldorf; Waldorf Education; Ritmo da manhã; Morning rhythm; Corpo e movimento; Body and movement; Antroposofia; Anthroposophy; Aprendizagem; Learning; CIENCIAS HUMANAS::EDUCACAO; 4. Educação de Qualidade